PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA DENGAN PROGRAM ADOBE FLASH CS6 BERBASIS KETERAMPILAN PROSES SAINS - Ferry Perdiansyah; Yetty Supriyati; I Made Astra (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
The purpose of this research is to produce a medium of learning physics that has been tested to support the learning process as well as determine the feasibility of the media that have been made . The method used in this research is the development of research methods ( Research and Development ) ASSURE model . The method used in collecting data through observation and documentation . The method of data analysis is the quantitative descriptive analysis techniques . Media created a computer -based media with a multimedia system , so that the subject is abstract indescribable in words can be described using animation or moving images . The program is created using Adobe Flash animation software that CS6 is assisted by several other supporting software . This research is expected to produce a learning program with a multimedia system that can be directly used by students and teachers as a tool in the learning process so that media -based learning Adobe Flash CS6 can facilitate learning and interesting physics , especially the material magnetic field to be one of the materials difficult to be digested by the students . The concept of learning media is not only facilitates the learning process but also to explore the physics potential of science process skills possessed by students . Keywords : media learning, Adobe Flash CS6 , science process skills